2022
DOI: 10.1002/sae2.12028
|View full text |Cite
|
Sign up to set email alerts
|

Application of microbial inoculants significantly  enhances crop productivity: A meta‐analysis of studies from 2010 to 2020

Abstract: Introduction: With the rapid development of microbial technology, microbial inoculant is considered as a promising tool in sustainable agricultural systems. Mechanisms by which microbial inoculants improve crop yield include improving plant nutrient availability and alleviating abiotic/biotic stresses (e.g., drought, salt and disease). However, the field efficacy of microbial inoculants remains inconsistent, which constrains large-scale adoptions. Identity of dominant mechanisms that underpin the positive impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 62 publications
3
44
1
Order By: Relevance
“…Our results showed that bacterial inoculants, in isolation or in a consortium, significantly promoted the functions (i.e., biofertilization and bioremediation) there were selective for when introduced into living soils. For example, applying single species showed an increased effect on plant growth promotion on average by 29%, which is similar to that reported in a recent meta-analysis (J. Li et al, 2022), which suggests the yield increase (32% on average) after the application of microbial inoculants.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results showed that bacterial inoculants, in isolation or in a consortium, significantly promoted the functions (i.e., biofertilization and bioremediation) there were selective for when introduced into living soils. For example, applying single species showed an increased effect on plant growth promotion on average by 29%, which is similar to that reported in a recent meta-analysis (J. Li et al, 2022), which suggests the yield increase (32% on average) after the application of microbial inoculants.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding soil organic matter and available N and P, the observed the significant and positive correlation between their contents and lnRR for biofertilization indicates that providing a soil environment that is relatively rich in nutrients is conducive to the function of inoculated agents. Indeed, a large number of studies have shown that measures such as organic fertilization can promote crop yields by regulating the bioavailability of soil nutrients and functional microorganisms (e.g., P-solubilizing bacteria) (Bi et al, 2020; K. Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy can be applied to identify key microbial genera associated with particular plant phenotypes (e.g., resistant to vascular plant pathogens [ 5 ]) or by transplanting beneficial bacteria from microbiomes of wild plant genotypes to cropped cultivars [ 72 ]. Such cultured bacterial consortia can also be ideal targets for the design of effective biofertilizers, biostimulants or biocontrol agents for a wide range of crops [ 73 ]. Therefore, the rebirth of microbial culture collections from specific plant ecological niches represents a valuable tool for increasing our understanding of the plant microbiome.…”
Section: Methodological Approaches To Study the Xylem Microbiotamentioning
confidence: 99%
“…In general, the host plant releases chemicals and root exudates into the soil which serve as a signal to initiate the recruitment of specific microbes in the rhizosphere, which subsequently enter inside the plant through the root and are then transported across the plant compartments through shoot into leaf, seeds, flower, etc. (Miransari and Smith,2014; Shade et al .,2017, Liu et al ., 2020). The plant microbiome assembly requires mutual recognition where microbes recognize chemical signals produced by the plant to respond, while the plant immune system ensures that only recognized microbes can colonize (Fitzpatrick et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%